Other subjectivities and a parable of African literature in “Jumping Monkey Hill” - Lombardo, Andrea Laura (2023)
In this article, we intend to examine the discursive-enunciative configuration of subjectivity, in particular, the materialization of cultural and gender identities in the story “Jumping Monkey Hill” by Chimamanda Ngozi Adichie, and its re-enunciation in the translated text into Spanish. In this sense, we use the contributions of feminist translation studies in its gender perspective, discourse analysis regarding the sociological analysis of ethos and queer theory with the purpose of evaluating the (a)symmetries of linguistic power, stereotypical representations and sexist vocabulary that represent women and the (in)visibility of gay and lesbian identities both in the original discourse and in the translation. In this theoretical-methodological framework and based on an analysis of cases, we will reflect on the way in which other subjectivities and identities that (re)interpret otherness and (de)stabilize the hegemonic categories of sexuality are translated and/or negotiated. On the other hand, we ponder on the ethics of translation that is displayed in the translated text from the re-enunciation of the ethos by the translator figure.